We Are All Teachers: A Collaborative Approach to Digital Collection Development. Issue 3 (2nd October 2017) - Shell-Weiss, Melanie; Benefiel, Annie; McKee, Kimberly
ABSTRACT: In libraries and archives, efforts to document underrepresented communities and diversify collections can be fraught with political tension. We explore an interdepartmental collaboration to create and preserve a digital collection documenting the Urban Native Relocation Program of the mid- to late-twentieth century in Grand Rapids, Michigan. Involving the Grand Valley State University Libraries, the Kutsche Office of Local History, and the university's Native American Advisory Board, the project serves as a model not just for collaborative collection development but also for community engagement and outreach. We find that process is as important as product in developing collaborative digital collections.